Pain Experience in Pancreatitis: Strong Association of Genetic Risk Loci for Anxiety and PTSD in Patients With Severe, Constant, and Constant-Severe Pain. (8th October 2021) - Dunbar, Ellyn K.; Greer, Phil J.; Amann, Stephen T.; Alkaade, Samer; Banks, Peter; Brand, Randall; Conwell, Darwin L.; Forsmark, Christopher E.; Gardner, Timothy B.; Guda, Nalini M.; Lewis, Michele D.; Machicado, Jorge D.; et al.
Abstract : INTRODUCTION: Recurrent acute pancreatitis (RAP) and chronic pancreatitis (CP) are progressive inflammatory syndromes with variable features. Pain is the primary feature that contributes to low physical and mental quality of life with a third of patients reporting severe pain. Pain experience is worsened by depression. Here, we tested the hypothesis that genetic risk of the psychiatric conditions of anxiety and post-traumatic stress disorder (PTSD) is associated with pain in CP and RAP + CP subjects. METHODS: The study cohort included phenotyped and genotyped RAP and CP patients from the North American Pancreatitis Study II of European Ancestry. Candidate genetic association studies were based on the absence of pain vs pain that is constant, constant-severe, or severe. Twenty-eight candidate genetic loci for anxiety and PTSD risk were identified in the literature and were the focus of this study. RESULTS: We identified 24 significant pain-associated single nucleotide polymorphisms within 13 loci across the 3 pain patterns in CP and RAP + CP ( P < 0.002). Thirteen anxiety or PTSD genes were within these pain loci indicating nonrandom associations ( P < 4.885 × 10 −23 ). CTNND2 was associated with all pain categories and all pancreatitis etiologies. Implicated systems include neuronal signaling ( HTR2A, DRD3, NPY, and BDNF ), hypothalamic-pituitary-adrenal axis ( NR3C1 and FKBP5 ), and cell-cell interaction ( CTNND2 and THBS2 ). DISCUSSION: A component of constant and severe pain in patients with RAP and CP is associated with genetic predisposition to anxiety and PTSD. Identification of patients at risk eligible for trials of targeted treatment as a component of a multidisciplinary pain management strategy should be formally evaluated.